Empowering Society 5.0: Digitalization, Sustainability, and Global Collaboration - Rafeah, Wahi; Noraziah, Abdul Wahab; Mohd Farid, Atan; Nadzirah, Jausus (Yayasan Fatih Al Khairiyyah, 2026)
Praise be to Almighty God for the completion of this book entitled Empowering Society 5.0: Digitalization, Sustainability, and Global Collaboration. This book emerges from the collective spirit of scholars, researchers, and practitioners from various countries who share insights, research findings, and best practices in addressing the dynamic challenges of the Society 5.0 era—a human-centered society supported by the advancement of digital technology.